VAGINAL DISCHARGE: IN THE GYNECOLOGIST - Soihet, Samoel (2015)
Vaginal discharge is the most common symptom for which women consult a gynecologist. It can occur as the only discomfort or be accompanied by other symptoms in the genitals. 75% of these patients are carriers of vaginal infections caused by Candida and / or Trichomonas, which are puriginosas, colibacillosis produced by burning, dyspareunia and odor, or Gardnerellas (Hemopbilus vaginalis) that only bad odors. The other flows are caused by the cervicitis ectropion without pathogens of importance, or by changing the ecology normally present in the vagina. The definitive diagnosis of the cause of vaginal discharge is: a. With the examination of the vagina with the speculum. b. The bacteriological study of the agents responsible. c. Determine the pH of the vaginal environment. Only then it can manage specific therapeutic and restore normal biological environment. Not all vaginal fluids indicate the presence of an infectious agent. All therapeutic attempt run by the same patient or the physician who does not identify the cause of vaginal discharge, can worsen the condition.